PEDAGOGICAL BASIS OF DEVELOPMENT OF STUDENTS’ CREATIVE ABILITIES - Quvvatova, Mohira Hikmatullayevna; Abdusalomova , Rayxona Abdurashid qizi (Educational Research in Universal Sciences, 2023)
The process of developing the creativity of future bachelors of pedagogical education requires scientific justification and methodological support due to insufficient cognitive, theoretical and practical significance. That’s why we tried to present our article on this topic. We can learn how to develop the creativity of future students.